Diagenetic controls over reservoir quality of tight sandstone in the lower Jurassic reservoir in the Lenghu area, the north margin of Qaidam basin - Li, Wenhuan; Hu, Dandan; Chang, Yuwen; Li, Ya’nan; Guo, Bin; Shi, Qi; Zhang, Bin (Frontiers in Earth Science, 2024)
The Lower Jurassic Reservoir (LJR) in the Lenghu area on the northern margin of the Qaidam Basin (NMoQB) has become the most promising target for hydrocarbon exploration. The reservoir has experienced complex diagenesis; however, the porosity evolution and the influence of different diagenesis events on reservoir densification remains unclear. In this study, various analytical methods was first used to clarify the diagenetic stage and sequence, establish a porosity evolution model, quantitatively analyze the time and influence of different diagenesis events on reservoir densification, and illustrate the densification mechanism of tight sandstone reservoir in the Lenghu area. The results showed that the dominant rock types in the LJR were feldspathic litharenite, followed by litharenite, lithic arkose, and a small amount of subarkose and sublitharenite. The reservoir is a typical tight sandstone reservoir (TSR), with average porosity and permeability of 5.5% and 0.08 mD, respectively. The pore types were primarily secondary pores, followed by residual intergranular pores and occasional fractures. Diagenesis of LJR has entered the meso-diagenetic stage A, with minor progression into meso-diagenetic stage B. Quantitative calculation showed that the initial porosity of LJR is 32.2%. In eo-diagenetic stage A, compaction is the main factor for porosity reduction. In eo-diagenetic stage B, the porosity loss rates caused by compaction and cementation were 81.5% and 11.8%, respectively. In this stage, the LJR in the Lenghu area has almost been densified, mainly affected by compaction, calcite cementation and clay minerals cementation. Additionally, cementation is an important factor causing reservoir heterogeneity and is dominated by calcite and clay mineral cementation. After entering the meso-diagenetic stage A, dissolution is the main diagenesis event, which can increase porosity by 6.0%. This stage is the critical period for forming high-quality reservoir of LJR in the Lenghu area, mainly in the 4400 m depth. In meso-diagenetic stage B, the influence of dissolution gradually decreased. Simultaneously, in this stage, the cementation of iron-bearing calcite further strengthened the densification of the LJR in the Lenghu area.